Choosing to Work? Mothers Return-to-Work Decisions, Social Class, and the Local Labor Market - Sihto, Tiina (Nordic Journal of Working Life Studies, 2015)
The aim of this study is to examine the ways in which social class shapes the return-to-work decisions of Finnish working-class and middle-class mothers, and how these decisions are structured by the constraints and opportunities mothers face in the local labor market. The focus of the study is in the local labor market of the city of Jyväskylä. The data consist of two semi-structured focus group interviews of 14 employed mothers of below school-age children. Using the framework of “gendered moral rationalities,” the study shows that there are similarities in mothers’ experiences, while the structural constraints mothers faced when deciding about the timing of returning back to work differ. The analysis highlights that the differences were not only dependent on social class but also on the situation in the local labor market. For working-class mothers, the most crucial issue was the financial strain that their staying at home caused to their families. For middle-class mothers, finding employment opportunities that would match their educational qualifications in the local labor market had been challenging, which affected their timing of returning back to work. The paper concludes that local labor market plays an important role in mother’s return-to-work decisions and should be explored further in differing geographical contexts.